Using simulated mergers to evaluate corporate diversification strategies - Silhan, P. A. (Institutional Knowledge at Singapore Management University, 1986)
This study suggests that simulated mergers can be used to help evaluate the effects of diversification on corporate performance. The results, which are consistent with a risk-reduction motive for conglomerate diversification, imply that conglomerate strategies focused on fewer and larger units may be advantageous in terms of certain measures of risk and return. Forecast error is used here to measure strategic risk, and return on equity is used to measure return.